Methodical System of Using Fitness Technologies in Physical Education of Students. - Zhamardiy, Valery; Griban, Grygoriy; Shkola, Olena; Fomenko, Olena; Khrystenko, Dmytro; Dikhtiarenko, Zoia; Yeromenko, Eduard; Lytvynenko, Andrii; Terentieva, Nataliia; Otravenko, Olena; Samokish, Ivan; Husarevych, Oleksandr; et al. (My University, 2020)
The article substantiates the model of the methodical system of using modern fitness technologies in physical education of students which takes into account all the components of the pedagogical process: the purpose, objectives, principles, methods, forms, and means of the preparation of future specialists’ personality who have perfect physical and health care competencies to apply fitness technologies in their own life. The methodical system is created on the basis of methodological, theoretical and practical concepts taking into account the humanistic, systemic, activity, personally oriented, innovative, cultural, and competency-based approaches. The model will contribute to the formation of the value-based attitudes of students to fitness technologies, the activation of students’ physical activity, and the formation of healthy lifestyle.
Methodical System of Using Fitness Technologies in Physical Education of Students / V. Zhamardiy, G. Griban, O. Shkola, O. Fomenko, D. Khrystenko, Z. Dikhtiarenko, E. Yeromenko, A. Lytvynenko, N. Terentieva, O. Otravenko, I. Samokish, O. Husarevych and Ihor Bloshchynskyi // International Journal of Applied Exercise Physiology (IJAEP). 2322-3537, 2020. – Vol.9. – No.5. – Р. 27–34. www.ijaep.com
Keywords: фізичне виховання, фітнес-технології, методична система, модель, студенти; physical education, fitness technologies, methodical system, model,students; физическое воспитание, фитнес-технологии, методический комплекс, модели, студенты